(3QSGdI aj HQGgjf CYeGd LOhd GdJbhje aj RjL MHT GdcGJHs - (3efUhQ Hf Ydj, CHh fUQ GHf YQGb , J fMh (B425 (3g`s
(3ChdgG (B:s
(3GdGbGhjd GdeNJdaI ai Ydd GdLOGhd GdGQHYI dMHT GdcGJH GdeYQhaI HLOhd GdJbhje s
(3BNQgG (B:s
(3aEPG Gf GdQGHY ceG PcQfG hGdKGdK ceG hUafG GdGf hbSefG GdeLJeY Ydi GdLjH cdg NQL GdPi jNQL ef GdYed GdChd hgPG cdai ajeG SCdJ Yfg hCfJ HMeO Gddg eSJZfi Yf LejY Pdc HeG MUd dc ef gPG GdYde GdTQja hgGgfG adfJe gPG Gdbhd s
(3HYK HgG GdeDda Edi CHj GdQMjGf GdHjQhfis
(3HgG CTcGd gfOSjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3Gdadcs